PERFORMA HARD MACHINING PADA AISI-01 ALLOY TOOL STEEL - Wiyana, Slamet (Mesin, 2016)
Machining of hard materials is an advanced machining technology. It can provide financial benefits of being able to reduce production costs. One of the limitations that the main problems is the formation of a white layer on the surface of product, formed during the machining process at high cutting temperatures. White layer is the layer structure has mechanical properties that hard and can to improve the wear resistance but also has a negative effect on the surface finish and fatigue strength of products. Because of its hard, white layer potential to cause failure cracks that ultimately lead to failure of the product. In this study aim to determine the effect of high cutting speeds on formation of white layer of AISI-01 alloy tool hardened steel 59.06 HRC using polycrystalline cubic boron nitride and CNGA-120 408 indexable cutting tool geometri. The methode of machining is variable speed machining, 80 m / min and 120 m / min. Scaning electron microscopes (SEM) was used to predict the surface topography which can explain the phenomenon of the white layer, while the composition was examined by EDX Ray. SEM observations showed that the application of higher cutting speeds can reduce the thickness of the white layer.Chemical composition of the material did not change significantly. Whereas the hardness test results show that this process does not lead to a decrease in material hardness values significantly.Keywords: white layer, hard machining, variable speed machinin